POLYA APPROACH IN PRACTICE: ANALYSIS OF PGMI STUDENTS' MATHEMATICS PROBLEM-SOLVING SKILLS - Putri Sekar Sari; Sabarudin; Siti Annisah; Thusy Siti Reihani (Universitas Majalengka, 2025)
Mathematical problem-solving ability is an important skill that every individual must have in learning mathematics. This research focuses on the practice of problem-solving based on the steps according to Polya. The aim is to describe the problem-solving skills of PGMI students in semester 3 of the 2024/2025 academic year and the obstacles they often face. This research is descriptive qualitative with purposive sampling technique and data collection methods through tests, interviews, observations, and documentation. The data will be analyzed using descriptive statistics, qualitative descriptive analysis, and content analysis. The results showed that the average student's problem-solving ability was 64% (high criteria). In detail, the average understanding of the problem reached 81% (very high), strategy planning 75% (high), plan execution 83% (very high), and re-examination only 0.4% (very low). The main obstacle that students often face is difficulty in understanding the problem, so they often make mistakes in planning and implementing solutions. In addition, students are also less careful in re-examining the answers that have been completed. The results of this study provide significance to improving the quality of mathematics learning in higher education, namely by designing more effective learning methods to improve students' problem-solving skills.